Orbit 2020
DOI: 10.1093/med-psych/9780197545959.003.0002
|View full text |Cite
|
Sign up to set email alerts
|

Rapport, Resistance, and Reactance

Abstract: This chapter outlines the definition of and use of rapport, based on principles of humanistic psychology. While rapport has been recognized in countless studies as a key feature of successful interrogations, it has historically been poorly defined and operationalized. This chapter uses real-world examples to highlight what rapport is and what it is not. The chapter also highlights key concepts and strategies drawn from the motivational interviewing literature that can be successfully applied to an interrogatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The concept of soft skills is a powerful way to conceptualise rapport as it implies rapport can be practised and developed into mastery in contexts like telehealth. 44 This applies equally to health professionals understanding telepresence without which rapport could not be realistically experienced. 37 , 45 , 46 Even with mastery though, rapport is not guaranteed, and requires attention in every interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of soft skills is a powerful way to conceptualise rapport as it implies rapport can be practised and developed into mastery in contexts like telehealth. 44 This applies equally to health professionals understanding telepresence without which rapport could not be realistically experienced. 37 , 45 , 46 Even with mastery though, rapport is not guaranteed, and requires attention in every interaction.…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 47 Although more research is needed into rapport and telehealth, researchers have identified the qualities required for successful rapport building and developed a checklist for telehealth skills. 44 , 48 Further research is also warranted to reflect the vital experiences that patients and families have of rapport in telehealth.…”
Section: Discussionmentioning
confidence: 99%
“…Two experienced ORBIT coders, worked independently to code each 15 min interview segment according to an ORBIT coding manual. The manual developed by Alison and Alison (2012) was used to code the behaviour of the participants in the interview. Interviewer behaviour was coded into three elements measuring the following: (i) Global Motivational Interviewing Scores (GMIS), (ii) Motivational Interviewing of Detainees: Assessment of Skills (MIDAS), and (iii) Interpersonal Behaviour Circle: Adaptive and Maladaptive – Interviewer (IBC-I).…”
Section: Methodsmentioning
confidence: 99%